The foot in diabetes - Boulton, A. J. M; Connor, Henry; Cavanagh, Peter R (John Wiley, 2000)
Reviews from previous editions: \"A book that should find a place on the bookshelves of all physicians who care for diabetic patients.\" Hospital Update \"I would thoroughly recommend that everyone read it if they do not wish to be left behind in this field.\" Journal of the Royal College of Physicians Diabetic foot problems are one of the most important long-term problems associated with diabetes. They can be a major cause of disablement and have serious economic consequences for health organisations. The Foot in Diabetes, Third Edition, has revised and expanded the popular previous editions to provide a fully comprehensive and contemporary review of the known causes of diabetic foot disease. * A practical guide to the clinical management of diabetic foot disease * Effectively illustrated * Comprehensively covers an area of considerable importance and interest * Contributions from experts in all relevant fields This essential text is of importance to all members of the diabetes specialist team including diabetologists, podiatrists, specialist nurses, district nurses, general practitioners, surgeons and clinical researchers.
Keywords: diabetes mellitus; diabetická noha; diabetologie; Diabetic Foot; diabetické angiopatie; nemoci nohy (od hlezna dolů); Foot Diseases; Diabetes Mellitus; Diabetic Angiopathies